Suprachiasmatic function in a circadian period mutant: Duper alters light‐induced activation of vasoactive intestinal peptide cells and PERIOD1 immunostaining. (26th November 2018) - Manoogian, Emily N. C.; Kumar, Ajay; Obed, Doha; Bergan, Joseph; Bittman, Eric L.
Abstract: Mammalian circadian rhythms are entrained by photic stimuli that are relayed by retinal projections to the core of the suprachiasmatic nucleus (SCN). Neuronal activation, as demonstrated by expression of the immediate early gene c‐fos, leads to transcription of the core clock gene per1 . The duper mutation in hamsters shortens circadian period and amplifies light‐induced phase shifts. We performed two experiments to compare the number of c‐FOS immunoreactive (ir) and PER1‐ir cells, and the intensity of staining, in the SCN of wild‐type (WT) and duper hamsters at various intervals after presentation of a 15‐min light pulse in the early subjective night. Light‐induced c‐FOS‐ir within 1 hr in the dorsocaudal SCN of duper, but not WT hamsters. In cells that express vasoactive intestinal peptide (VIP), which plays a critical role in synchronization of SCN cellular oscillators, light‐induced c‐FOS‐ir was greater in duper than WT hamsters. After the light pulse, PER1‐ir cells were found in more medial portions of the SCN than FOS‐ir, and appeared with a longer latency and over a longer time course, in VIP cells of duper than wild‐type hamsters. Our results indicate that the duper allele alters SCN function in ways that may contribute to changes in free running period and phase resetting. Abstract : Duper mutant hamsters have a fast circadian clock and enhanced phase delays in response to a light pulse delivered in the early subjective night (Circadian Time 15). Top, the light signal is relayed from the eye to the suprachiasmatic nucleus (SCN), which serves as a master pacemaker. Subordinate circadian oscillators in other brain areas, including the paraventricular nucleus (PVN), adjust their phase in response to SCN input. As a result, behavioral rhythms show a phase delay (horizontal red arrow) that is greater in duper (middle panel) than wild‐type (bottom panel) hamsters. Resetting of the pacemaker of mutant hamsters differs from that in wild type: dupers show increased activation (as reflected by greater c‐FOS immunoreactivity) and clock gene expression (as reflected by PER1 immunoreactivity) in the ventral core (green) and dorsal shell (blue) neurons of the SCN at various time points sampled after the light pulse (vertical arrows). Activation of VIP neurons of the core SCN is specifically affected by the duper mutation.